PSYCHOLOGICAL PECULIARITIES OF SOCIAL ADAPTATION OF MILITARY FAMILY MEMBERS IN WARTIME - Liubyva , Olena (Collection of scientific papers «ΛΌГOΣ», 2023)
The wartime period is accompanied not only by physical and psychological challenges for the serviceman, but also affects his family. Family members of military personnel face significant changes in their lives that can cause difficulties in social adaptation. This article will examine the psychological peculiarities of social adaptation of military family members in wartime, as well as provide a review of the literature on the topic.